2018
DOI: 10.1108/jocm-07-2017-0286
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organizational culture and job design on job commitment and human resource performance

Abstract: Purpose The purpose of this paper is to analyze the relationship between Job Design, Job Commitment and Organizational Culture with Human Resource Performance: a study of the construction services provided by national consultants. Design/methodology/approach The research population consisted of all employees of a national company offering consultation services, from four big Indonesian State-Owned Enterprises Contractors: PT. Yodya Karya Company, PT. Hutama Karya, PT. Adhy Karya, PT. Waskita Karya Referring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 80 publications
9
62
0
10
Order By: Relevance
“…Research has found that job design can have a profound impact on employee attitudes and behaviour (Campion, Mumford, Morgeson & Nahrgang, 2005) at both the individual and organisational level (Fried & Ferris, 1987;Humphrey et al, 2007). It is an important determinant of employees' affective commitment (Dunham, Grube & Castañeda, 1994;Raharjo, Solimun & Fernandes, 2018), job satisfaction (Lawler, 1969;Hackman & Oldham, 1974Brass, 1985;Bhuidan & Buklend, 2002;Glisson & Durick, 1988;Fahr, 2011), higher employee motivation (Hackman & Oldham 1974Campion & Thayer, 1987;Humphrey et al, 2007;Cheng & Lu, 2012), increased job performance (Lawler, 1969;Hackman & Oldham, 1974Brass, 1985;Campion & Thayer, 1987), career incentives (Kaarboe & Olsen, 2006), greater involvement and lower absenteeism (Campion & Thayer, 1987;Hackman & Oldham, 1974, lower turnover (Hackman & Oldham, 1974, higher engagement and performance ratings, and enacting more organisational citizenship behaviours and engaging in fewer deviant behaviours (Shantz, Alfes, Truss & Soane, 2013). However, Parker, Wall and Corderly (2001) propose that the collective effects of the core job characteristics on affective responses (satisfaction and motivation) are largely supported in the relevant research, but those for behaviour (i.e., work performance, turnover, and absence) less consistently so.…”
Section: Job Design and Work-related Attitudes In The Ict Sectormentioning
confidence: 99%
“…Research has found that job design can have a profound impact on employee attitudes and behaviour (Campion, Mumford, Morgeson & Nahrgang, 2005) at both the individual and organisational level (Fried & Ferris, 1987;Humphrey et al, 2007). It is an important determinant of employees' affective commitment (Dunham, Grube & Castañeda, 1994;Raharjo, Solimun & Fernandes, 2018), job satisfaction (Lawler, 1969;Hackman & Oldham, 1974Brass, 1985;Bhuidan & Buklend, 2002;Glisson & Durick, 1988;Fahr, 2011), higher employee motivation (Hackman & Oldham 1974Campion & Thayer, 1987;Humphrey et al, 2007;Cheng & Lu, 2012), increased job performance (Lawler, 1969;Hackman & Oldham, 1974Brass, 1985;Campion & Thayer, 1987), career incentives (Kaarboe & Olsen, 2006), greater involvement and lower absenteeism (Campion & Thayer, 1987;Hackman & Oldham, 1974, lower turnover (Hackman & Oldham, 1974, higher engagement and performance ratings, and enacting more organisational citizenship behaviours and engaging in fewer deviant behaviours (Shantz, Alfes, Truss & Soane, 2013). However, Parker, Wall and Corderly (2001) propose that the collective effects of the core job characteristics on affective responses (satisfaction and motivation) are largely supported in the relevant research, but those for behaviour (i.e., work performance, turnover, and absence) less consistently so.…”
Section: Job Design and Work-related Attitudes In The Ict Sectormentioning
confidence: 99%
“…From a social perspective, an organization's culture is a living system that is a matter of priority for those managers who want to build a strong structure of norms and values within an organization. While sharing it to those working in different levels within the organization, to become not only a system of thinking approach but protrude the "life" of an organization (Raharjo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve effective and efficient organizational goals require human resources or employees who have high commitment (Allen_and_Meyer, 1990). The commitment of human resources significantly affects the performance of human resources of an organization (Raharjo et al, 2018). Organizational commitment plays a significant role in organization.…”
Section: Introductionmentioning
confidence: 99%